Pentingnya Pendidikan Konservasi Untuk Menjaga Lingkungan Hidup (Studi Kasus di Desa Cidahu, Kabupaten Kuningan) - Rifqie Mardiansyah Purmadi; Dewa Made Juli Santika; Arum Sekar Wulandari (Jurnal Pusat Inovasi Masyarakat (PIM), 2020)
Education is an important role in the enhancement and development of human resources of a nation. Conservation education is an education that expects a change in behaviour, attitudes and thinking, especially related to the management of natural resources and their ecosystem. The other potential of Cidahu village is the great attention to the development of the village both from citizens and village officials. Conservation education is one of the programs conducted in Cidahu village. This activity raised the theme of "I love nature" with the subtheme "I love the Environment" and "I Love the Woods". This activity aims to increase the knowledge and concern of elementary school students (SD Cidahu and MI PUI Cidahu) in protecting the environment. This activity is carried out by way of delivering material related the biotic and abiotic environment, how to maintain and the denger of polluting the environment, followed by questions and answers about the topic. Results of this activities show that conservation eucation can increase students knowladge and change attitudes toward better environmental protection. Keywords: Cidahu village, conservation education, environment